THE EXPRESSION OF POLITENESS USED BY GLORIA IN DEMI UCOK MOVIE - Lisbet Ambarita; Juli Rachmadani Hasibuan (State University of Medan, 2016)
This study deals with The Expression of Politeness used by Gloria in Demi Ucok Movie. The data of this study were the utterances in Demi Ucok by Gloria. The utterances which contained principles politeness were identified and analyzed. This study applied descriptive qualitative method which is concerned in developing explanation of types of principles politeness to help us understand the principles politeness in which how people used it. The descriptive qualitative was used in this research in which the writer analyzed the data and described the dominant based on its Principles Politeness classification to aim at maximize the benefit to other, maximize praise of other, maximize dispraise of self, maximize agreement between self and other, and maximize sympathy between self and others which had found in utterances in Gloria by Demi Ucok. The findings show of 78 utterances, they were shown by Tact Maxim (34), followed by Modesty Maxim (13), Approbation (13), whereas Sympathy Maxim (12), and Agreement (6) and the principles politeness of Demi Ucok by Gloria mostly showed Tact Maxim as minimize cost to self and maximize benefit to other, and found the implication to solve the problem.